Music, the Arts, and Ideas: Patterns and Predictions in Twentieth-Century Culture - Meyer, Leonard B. (Chicago, IL University of Chicago Press, 1994)
Meyer makes a valuable statement on aesthetics, criteria for assessing great works of music, compositional practices and theories of the present day, and predictions of the future of Western culture. His postlude, written for the book's twenty-fifth anniversary, looks back at his thoughts on the direction of music in 1967.
Keywords: 20th Century (1901-2000); Music philosophy and esthetics